Surviving in hot and cold: psychrophiles and thermophiles from Deception Island volcano, Antarctica - Bendia, Amanda G.; Araujo, Gabriel G.; Pulschen, Andre A.; Contro, Bruna [UNESP]; Duarte, Rubens T. D.; Rodrigues, Fabio; Galante, Douglas; Pellizari, Vivian H. (Springer, 2018)
Polar volcanoes harbor unique conditions of extreme temperature gradients capable of selecting different types of extremophiles. Deception Island is a marine stratovolcano located at Maritime Antarctica that is notable for its pronounced temperature gradients over very short distances, reaching values up to 100 degrees C in the fumaroles, and subzero temperatures next to the glaciers. Due to these characteristics, Deception can be considered an interesting analogue of extraterrestrial environments. Our main goal in this study was to isolate thermophilic and psychrophilic bacteria from sediments associated with fumaroles and glaciers from two geothermal sites in Deception Island, comprising temperatures between 0 and 98 degrees C, and to evaluate their survivability to desiccation and UV-C radiation. Our results revealed that culturable thermophiles and psychrophiles were recovered among the extreme temperature gradient in Deception volcano, which indicates that these extremophiles remain alive even when the conditions do not comprise their growth range. The viability of culturable psychrophiles in hyperthermophilic environments is still poorly understood and our work showed the importance of future studies about their survival strategies in high temperatures. Finally, the spore-forming thermophilic isolates which we found have displayed good survival to desiccation and UV-C irradiation, which suggests their potential to be further explored in astrobiological studies.
Keywords: Polar volcano; Deception Island; Temperature gradient; Extremophiles; Astrobiology